Batik Lasem educational Game as a means of strengthening the dimension of Global Diversity in elementary school students - Yanti Sulistyowati; Eko Handoyo; Tri Joko Raharjo (Universitas Negeri Semarang, 2026)
Globalization presents both opportunities and challenges in shaping the identity of elementary school students, particularly in maintaining cultural awareness while developing global perspectives. The dimension of global diversity (berkebinekaan global) in the Pancasila Student Profile demands learning innovations that bridge local culture and global values. This study aimed to develop and examine the effectiveness of an educational game based on Batik Lasem in strengthening the global diversity dimension of elementary school students. Batik Lasem was chosen because it represents the acculturation of Javanese, Chinese, and Arabic cultures, making it an authentic medium for cultivating tolerance and respect for cultural differences. The study employed a quasi-experimental design with a pretest-posttest non-equivalent control group. The sample consisted of 64 fifth-grade students from two elementary schools in Rembang Regency, selected through purposive sampling. The experimental group (n=32) used the Batik Lasem educational game, while the control group (n=32) used conventional methods. Data were collected using a validated global diversity attitude scale and a cultural knowledge test, then analyzed using an independent samples t-test and N-Gain analysis. The results showed a significant difference between the two groups (t=7.842; p<0.001) with an effect size of Cohen's d=1.94 (very large category). The N-Gain of the experimental group was 0.71 (high category), while the control group was 0.32 (medium category). These findings indicate that the Batik Lasem educational game is effective as a means of strengthening the global diversity dimension in elementary school students, while preserving local cultural heritage in the digital era.